Facial Recognition in Multimodal Biometrics System for Finger Disabled Applicants - Faddly Mazlan; Afdallyna Harun; Saiful Izwan Suliman (Institute of Advanced Engineering and Science, 2017)
Citizen identification in Malaysia is managed by Jabatan Pendaftaran Negara (JPN); a Malaysian Government Agency responsible in producing a national identification card called MyKad which contains textual information of the MyKad holder as well as fingerprint data. The current business modal solely relies on fingerprint identification as recognition process which presents limitations to Malaysian citizens who have finger disabilities. Currently, this matter is addressed by having applicants provide proof of identification which is then verified by the agency within three months. To improve efficiency of this process as well as making it friendlier for applicants to apply their MyKad, the use of facial recognition is proposed as a potential solution. A series of study was conducted with JPN, which intends to measure the reliability of a multimodal biometrics system in JPN environment for finger-disabled applicants. Findings demonstrate that Multimodal Biometrics System using Facial Recognition is reliable for individual identification.